METAFİZİK NEDİR? İBN SÎNÂ'NIN KİTÂBU'Ş-ŞİFÂ EL-İLÂHİYYÂT'I BAĞLAMINDA BİR TAHLİL - (:unkn) unknown (My University, 2014)
İbn Sînâya göre metafizik, mevcudu konu edinmektedir ve varlık anlamının farklı belirlenimlerini araştırmaktadır. Bu bağlamda metafizik varlık anlamının saf halini, kaynak ve ilkesini, varlık (vucud) bireylerinin bu ilkeden nasıl çıktığını, gerçek kıldığı mahiyetlerle hangi kısımlara ayrıldığını incelemektedir. Diğer deyişle metafizik, mevcut olmak bakımından mevcudun genel durumlarını ve varlığın ilkelerini incelemektedir. Ayrıca metafizik, teorik felsefî disiplinlerin zirvesinde bulunması ve konusunun kapsayıcılığı nedeniyle tikel felsefî ilimlerin ilkelerini de temellendirir. Böylece metafizik mevcudun genel durumları, Tanrı ve ayrık nedenleri ve tikel ilimlerin ilkelerini incelemek olmak üzere esas itibariyle üç işlevi yerine getirir. Bu anlayış, İbn Sînâyı, Kindî vb. metafiziği bir teoloji olarak kavrayan filozoflardan ayırarak Fârâbîye bağlar. Bu makale, Kitâbuş-Şifa Metafizikten hareketle İbn Sînânın metafizik tasavvurunu incelemektedir.

According to Ibn Sina, metaphysics is concerned with the existent and the different determinations of the meaning of existence. In this respect metaphysics investigates the pure nature of the meaning of existence, its source and principles, how individual beings have emancipated from this principle, the essences it has brought to existence and its partition. In other words, metaphysics analyzes the general conditions of the existent inasmuch it exists, and the principles of existence. Furthermore because of its place on top of the theoretical philosophic disciplines and its comprehensive subject, metaphysics establishes the principles of the particular philosophical sciences. Thus metaphysics functions in three aspects, namely the general states of existence, God and its separate causes, and the principles of particular sciences. This understanding connects Ibn Sina with Farabi rather than philosophers who comprehend metaphysics as a theology like Kindi and others. This article examines how Ibn Sina conceives metaphysics with regard to his Kitab al-Shifa al-Ilahiyyat.
What is Metaphysics? An Analysis in the Context of Kitab al-Shifâ al-İlahiyyat of Ibn Sina
Keywords: Din Bilimi